The Thule Migration: A Culture in a Hurry? - Park Robert W. (Open Archaeology, 2023)
The process by which the Thule Inuit migrated from the region around Bering Strait into Arctic Canada and Greenland, which is notable for its logistical complexities, the varied and difficult regions traversed and then populated, and for the enormous distance covered, is almost invariably described in terms emphasizing the pace at which it took place. The most common description is “rapid,” and some descriptions conclude it may have been accomplished within just a few decades, despite researchers not having explored the logistical and demographic implications of that inference. This article explores several possible meanings of “rapid” in the context of the Thule migration and reviews the evidence that is informative concerning its pace, including radiocarbon dates, historical encounters, logistics, and demography. It concludes that the Thule Inuit may indeed have felt a sense of urgency to expand into new regions, but they did this at a far slower pace than most researchers have concluded, over centuries rather than decades.